2016
DOI: 10.15625/0866-708x/54/6/8375
|View full text |Cite
|
Sign up to set email alerts
|

A Miniaturization of Microstrip Antenna Using Negative Permitivity Metamaterial Based on CSRR-Loaded Groundfor Wlan Applications

Abstract: A microstrip antenna using negative permittivity metamaterial based on complementary split ring resonator (CSRR)-loaded ground has been investigated in order to miniaturize the size and improve the antenna characteristics. The antennas are designed on FR4 material and simulated results are provided by HFSS software. The metamaterial antenna is reduced 77 % the antenna size compared to the normal microstrip antenna. Furthermore, compared with the normal microstrip antenna, the antenna characteristics of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Studies on antennas have been reported by many researchers who seek to enhance antenna properties such as bandwidth, gain, efficiency and antenna size. In this connection, a rectangular patch antenna associated with left-handed medium was investigated in [9]. The results showed the antenna to be more directive and the gain to be high, although size reduction remained a major chal- lenge.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on antennas have been reported by many researchers who seek to enhance antenna properties such as bandwidth, gain, efficiency and antenna size. In this connection, a rectangular patch antenna associated with left-handed medium was investigated in [9]. The results showed the antenna to be more directive and the gain to be high, although size reduction remained a major chal- lenge.…”
Section: Introductionmentioning
confidence: 99%
“…To study the behavior of the planar metamaterial structure, the simulation of the CSRR unit cell has been carried out as described in our previous study [16]. As the simulation model shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The radius of rounded contour r = 24.5 mm (0.196λ) is selected for the accepted S-parameters and minimum antenna size. We note that compared to the size of conventional patch antenna elements (without CSRR loaded ground), which is calculated using the formulas as shown in [17], the size of an individual patch antenna with CSRR loaded ground is reduced up to 77 % [16].More details on the individual patch antenna design can be found in our previous work [16].…”
Section: Antenna Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of unit cells of metamaterials is based on the calculation of size and simulation of unit cells, so that the parameters ε and μ of these unit cells will satisfy the requirements at the expected resonant frequency. Depending on the structure and size of each unit cell, we can obtain different ε, μ, and resonant frequencies f. For each unit cell type, the dimensions of unit cell can be adjusted to satisfy condition at resonant frequency f r [25]. A unit cell is usually smaller than 1/10 of the operating wavelength (see Figure 7), depending on the shape of the metamaterial, but the unit cell size is different [19,20,26].…”
Section: Unit Cell Of Metamaterialsmentioning
confidence: 99%